RANCANG BANGUN MESIN PERONTOK PADI DENGAN MENGGUNAKAN MESIN PENGGERAK BENSIN BERDAYA 6 HP - Angga Prayogi Purba; Jhon Sufriadi Purba; Danie E.T. Siburian (Journal of Research and Publication Innovation, 2025)
This research is based on experience in an agricultural area in the field of rice farmers who are still lagging behind in the field of technology in agricultural processes in that area. Considering that the agricultural land in North Sumatra is around 766,760 hectares, there are still areas that are lagging behind in rice harvesting equipment, where farmers still harvest manually, which is considered to be less effective. In an effort to increase the efficiency of the rice harvest process and yields, tools are needed to help speed up the harvest process using a Rice Thresher Machine which will be distributed in the Simalungun area, North Sumatra. Precisely in Sibuntuon village, Kec. Dolog Pardamean, Kab. Simalungun, Prov. North Sumatra.